Correlations between dietary intake of different minerals with their concentrations in serum, hair and milk in Murrah buffaloes - MAAN, N S; MANDAL, A B; DAHIYA, D S; PANWAR, V S; KHATTA, V K (The Indian Journal of Animal Sciences, 2013)
The samples of blood, hair and milk along with feeds and fodders consumed by the buffaloes (156 milch, 77 heifers) were collected at random. The samples were analyzed for calcium (Ca), phosphorus (P), zinc (Zn), copper (Cu), iron (Fe) and manganese (Mn) contents. The intake of different minerals was calculated from data of intake of different feeds and fodders and their mineral composition. Correlations were drawn between dietary intake of different minerals and their concentrations in serum and hair of heifers and in milk for milch animals. In milch buffaloes, serum P had inverse correlation while Mn concentration in hair had positive correlation with Ca intake. Mn intake had positive correlation with its concentration in hair and also with hair Fe, Zn and P, but negative correlation with serum and milk P. Intake of Fe had negative correlation with hair concentration but positive with its concentration in serum. Dietary intake of Cu did not influence its concentration in serum, hair and milk but reduced hair Fe significantly. Serum Zn concentration increased significantly with its dietary supplies but had negative correlations with serum Cu, serum Fe, and Mn in milk or hair. Positive correlations existed between intakes of Fe and Cu in serum or milk, serum Fe, Mn in serum, milk and hair while negative correlations were observed serum and milk P, and Fe in hair. In heifers, serum and hair Ca has negative correlation with Ca intake. Intake of Zn, Mn or Cu did not influence their concentration in serum or hair. Study concluded that significant correlation exists between dietary intake and level of minerals in hair, serum and milk and also amongst themselves. Therefore, there is a possibility of predicting intake of certain minerals from hair, serum or milk mineral concentration.